Hubungan Motivasi Kerja Pegawai dengan Pelayanan Publik - Siti Ismaryati (Universitas Riau, 2010)
Theoretically, work motivation has an effect on public service quality. The research aimsto finding out whether in case of garbage services in Depok City such kind of effect also occur. Theresearch approach is quantitative. Independent variable is work motivation, and dependent vari-able is public service quality in garbage collection. There are 131 respondents consisting of govern-ment employees and members of community. The primary research instrument is questionnaire.Data are analyzed using correlation analysis, determination analysis, and regression analysis aswell. The research result that there is significant effects of government employee work motivationon public service quality in garbage collection in Depok City. In such manner, the effects of govern-ment employee work motivation is the result of condition and interaction among dimensions ofgovernment employee work motivation, namely: the arousal, direction, and persistence of effort inwork settings.” Research findings has enhanced the existing theory of work motivation and enrinchedsuch a theory as well by delineating some new aspects for analyzing the effects of work motivationon public service quality. Such new aspects consist of the priority of public interests, the opportu-nity of promotion and performance reward, and organizational attachment.